Characterization of a New Pm2 Allele Conferring Powdery Mildew Resistance in the Wheat Germplasm Line FG-1 - Ma, Pengtao; Xu, Hongxng; Li, Lihui; Zhang, Hongxia; Han, Guohao; Xu, Yunfeng; Fu, Xiaoyi; Zhang, Xiaotian; An, Diaoguo (Frontiers in Plant Science, 2016)
Powdery mildew has a negative impact on wheat production. Novel host resistance increases the diversity of resistance genes and helps to control the disease. In this study, wheat line FG-1 imported from France showed a high level of powdery mildew resistance at both the seedling and adult stages. An F2 population and F2:3 families from the cross FG-1 × Mingxian 169 both fit Mendelian ratios for a single dominant resistance gene when tested against multiple avirulent Blumeria tritici f. sp. tritici (Bgt) races. This gene was temporarily designated PmFG. PmFG was mapped on the multi-allelic Pm2 locus of chromosome 5DS using seven SSR, ten SNP-derived and two SCAR markers with the flanking markers Xbwm21/Xcfd81/Xscar112 (distal) and Xbwm25 (proximal) at 0.3 and 0.5 cM being the closest. Marker SCAR203 co-segregated with PmFG. Allelism tests between PmFG and documented Pm2 alleles confirmed that PmFG was allelic with Pm2. Line FG-1 produced a significantly different reaction pattern compared to other lines with genes at or near Pm2 when tested against 49 Bgt isolates. The PmFG-linked marker alleles detected by the SNP-derived markers revealed significant variation between FG-1 and other lines with genes at or near Pm2. It was concluded that PmFG is a new allele at the Pm2 locus. Data from seven closely linked markers tested on 31 wheat cultivars indicated opportunities for marker-assisted pyramiding of this gene with other genes for powdery mildew resistance and additional traits.